BIMBINGAN TEKNIS KURIKULUM MERDEKA BELAJAR BAGI GURU DI RA AL KAUTSAR - Deswita Deswita; Rifa Atiyyah; Arie Purwa Kusuma; Nurina Kurniasari Rahmawati (Journal of Social Outreach, 2023)
Supporting Indonesia's educational vision, and as part of efforts to restore learning, the Merdeka Curriculum (which was previously referred to as a curriculum prototype) was developed as a curriculum framework that is more flexible, while also focusing on essential material and developing the character and competence of students. Efforts to run an independent curriculum at this time, is one of the efforts to be able to implement it in the implementation of the curriculum, and teachers are very important in playing and implementing this independent curriculum to the fullest and can run well. The implementation of Community Service (PKM) carried out by STKIP Kusumanegara Lecturers was in the form of training on the implementation of the independent curriculum for teachers delivered to teachers under the auspices of all RA (Raudhatul Atfal) in Bogor district. This training is delivered in a systematic and simple manner so that it can be understood easily and can have a significant impact in realizing education for students. The result is an increase in teacher understanding in three aspects; (1), theoretically, (2), how to implement it, and (3), how to develop a curriculum. Keywords: Implementation, Curriculum, Free Learning, Training